1981
DOI: 10.1021/bi00527a022
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of meso-.alpha.,.epsilon.-diaminopimelate decarboxylase reaction: the first evidence for pyridoxal 5'-phosphate dependent decarboxylation with inversion of configuration

Abstract: The stereochemistry of the decarboxylation of meso-alpha,epsilon-diaminopimelate catalyzed by meso-alpha,epsilon-diaminopimelate decarboxylase (EC 4.1.1.20) of Bacillus sphaericus was determined by stereochemical analyses of [6-2H]-L-lysine produced by the reaction in D2O. The product [6-2H]-L-lysine was converted to levorotatory methyl 5-phthalimido[5-2H]valerate by the reactions not affecting the absolute configuration of the asymmetric carbon atom. By contrast, methyl 5-phthalimido[5-2H]valerate derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The product will then consist entirely of molecules that are correspondingly deuterated, and is therefore not only chiral but its optical activity will, in all likelihood, be measurable (subject to the sensitivity of the detection instruments). The chirality of the product can then be determined by the classical method of measuring optical activity followed by assignment of configuration by comparison of this activity with that of standards of known configuration (4,12,14). Alternatively, nmr methods can be applied (9,17) in the configurational assignment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The product will then consist entirely of molecules that are correspondingly deuterated, and is therefore not only chiral but its optical activity will, in all likelihood, be measurable (subject to the sensitivity of the detection instruments). The chirality of the product can then be determined by the classical method of measuring optical activity followed by assignment of configuration by comparison of this activity with that of standards of known configuration (4,12,14). Alternatively, nmr methods can be applied (9,17) in the configurational assignment.…”
Section: Discussionmentioning
confidence: 99%
“…L-Ornithine (14) in deuterium oxide gave (-)-(l-2H)putrescine dihydrochloride (15), L-(2-2H)ornithine in water gave (+)-(l-2H)putrescine dihydrochloride. The ORD curves of the two samples are shown in Fig.…”
Section: +Nh3 ( * ) -( 2 -2~)~m I T H I N E Monohydrochloridementioning
confidence: 99%
“…Therefore, amino acid racemase with low substrate specificity probably belongs to the same family of proteins as alanine racemase: a unique family containing only alanine racemase, mammalian ornithine decarboxylase, and meso-␣,⑀-diaminopimelate (DAP) decarboxylase with little similarity to other PLP enzymes (43). We have shown that the decarboxylation of DAP catalyzed by DAP decarboxylase proceeds through inversion of the configuration of the ␣-carbon of DAP (29). This indicates that the enzyme function must be conducted on both sides of the plane of the substrate⅐PLP complex so as to decarboxylate on one side and to introduce a proton on the other side.…”
Section: Stereospecificity Of Amino Acid Racemases For Hydrogen Abstrmentioning
confidence: 99%
“…A DAPDC reaction mechanism has been previously proposed (5,6). The reaction mechanism is thought to be initiated by the formation of a Schiff base between PLP and a conserved active site lysine from the (Y/F)AXKA motif (7).…”
mentioning
confidence: 99%